Reduction of Radioactive Cesium Concentration in Water Using Iron Oxide Nanoparticles - Ali, Ahmed H.; Al-Mashhadani, Asia H. (Iraqi Journal of Science, 2026)
The work focuses on the pressing issue of pollution caused by radionuclides, which causes significant hazards to humans, public health and the environment. Radioactive cesium (Cs) is among these pollutants. It is particularly hazardous due to its high mobility and long half-life (30 years). To remove cesium from radioactive waste, traditional treatment methods were used, such as ion exchange and coagulation, both generate large quantities of radioactive sludge and are energy-intensive. To overcome this problem, a method can be employed using nano-adsorbents, such as iron oxide-based materials like magnetite. This research explores the application of iron oxide nanoparticles (Fe3O4) as a novel approach to remove radioactive cesium (Cs) from contaminated water. The use of nano-adsorbents represents a more efficient and sustainable option. This work examines the removal of Cs from water using nanoparticles (Fe3O4) and magnetic separation. Iron oxide nanoparticles were synthesized via a chemical co-precipitation method and characterized using various techniques, including Field Emission Scanning Electron Microscopy (FESEM), X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Energy Dispersive X-ray Spectroscopy (EDX), and Atomic Force Microscopy(AFM). The results approved the successful preparation of nano-Fe3O4 with desired properties, such as morphology, functionalization, and crystalline structure. Adsorption parameters, such as contact time, pH, initial activity, and concentration, were experimentally investigated. The adsorption efficiency of Cs removal increased with increasing the mass of nano-Fe3O4, with an optimal removal value of 0.5g of adsorbent. Furthermore, the study examined aqueous pH and the influence of Cs-137 specific activity on the remediation treatment, showing promising results under different conditions. The Cs removal efficiency of 84.79% was notably maximum at 0.5g adsorbent mass with a pH of 9. Additionally, the effect of contact time on the remediation treatment was investigated revealing maximum removal efficiency at 1440 minutes, after which it plateaued. These results underscore the efficacy of Fe3O4 nanoparticles in capturing Cs from aqueous solutions, which makes it easier to remove radioactive waste. Using iron oxide nanoparticles as effective sorbents for processing radioactive materials, 137Cs-contaminated water, proved to be a promising way to mitigate environmental impacts and health hazards associated with radionuclide contamination.